PERBEDAAN KARAKTERISASI DAN SKRINING FITOKIMIA EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangsotana Linn) YANG DIPEROLEH DARI KABUPATEN TABANAN DAN KABUPATEN KARANGASEM, PROVINSI BALI - Chintya Sandra Bhuana, Ni Putu; Ayu Dewi Wijayanti, Ni Putu; Dewantara Putra, I G. N. Agung (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 2 Juli 2013, 2013)
Mangosteen peel has been studied to contain many chemical constituents. However, differences in the geographical location of a plant can result in variations in the content of a plant metabolites. This study aimed to determine differences in the characteristics of the extract as well as content owned chemical peel ethanol extract of mangosteen (Garcinia mangostana L.) were obtained from Tabanan and Karangasem regency, Bali province. This study is experimental designed.  Extraction process used the method of maceration with 70% ethanol. Organoleptic characterization of the extract was conducted. Water content, content of water-soluble extract and ethanol soluble extract were also determined. Phytochemical screening of the extract covered the content of alkaloids, glycosides, flavonoids, saponins, phenolic, and steroids / terpenoids. The results showed that the ethanol extract of mangosteen peel taken from Tabanan regency contain saponins, alkaloids, flavonoids, phenolics, terpenoids, and glycosides, while the ethanol extract of mangosteen rind taken from Karangasem regency contain saponins, alkaloids, flavonoids, phenolic, terpenoids. The ethanol extract of mangosteen peel taken from Tabanan regency has a different chemical content with ethanol extract of mangosteen peel taken from Karangasem regency.
Keywords: mangosteen, ethanol extract, characterization extract, Phytochemical screening, tabanan, karangasem